Terjemahan metafora Thirukkural dari Bahasa Tamil ke Bahasa Melayu / Anurani Nagarajan - Anurani, Nagarajan (2019)
This study form on the translation of Thirukkural Tamil metaphor into Malay language. The main purpose of this study was to analys the strategies used in translating Tamil metaphor into Malay according to Thirukkural Trilingual book translation. The sample was selected based purposive sampling which focused on 40 Tamil metaphor. The method used in this study is descriptive based on the method. The process of analyzing these translation strategies are based on the bahasa Melayu version 7 of Larson’s Taxonomy (1980). Based on the translation strategy analysis, the accuracy of Tamil metaphor was compared of the Malay Metaphor translation evaluated. The findings of this study showed that the most frequent translation strategies used by the translator is the first strategy which is word for word translation in which the word order is preserved and the words translated singley by their most common meanings at of context with a total of 25 times (62.5%).